If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
y-1 = (2/3)*(x-3) // - (2/3)*(x-3)
y-((2/3)*(x-3))-1 = 0
(-2/3)*(x-3)+y-1 = 0
y-2/3*(x-3)-1 = 0
y-2/3*(x-3)-1 = 0
y-2/3*x-1+2 = 0
y-2/3*x+1 = 0
y-2/3*x+1 = 0
y-2/3*x+1 = 0 // - y+1
-2/3*x = -(y+1) // : -2/3
x = (-(y+1))/(-2/3)
x = 3/2*(y+1)
x = 3/2*(y+1)
| 3z/10-4=9 | | 8+2-y=0 | | 4(-3)-3(4)-12(-1)= | | 15.00/0.25 | | 8y-5x=4 | | 3t+15-6=9 | | 3333= | | 30-3(-2x+4)=5(x+9) | | z/8-1=7 | | -2/8=-30/x | | 4(3x-5)=23 | | .05(8x+4)-(3x-9)= | | x-9/3=15/13 | | x^2-2x+98.777777777777777=0 | | 6+(5k-2)= | | y=0.8333333333+0.5x | | 4(x-1)=81 | | 6x(-x)=3x+8 | | 4x-17=38 | | y-4=7(0-6) | | 125oz=cup | | 2(t-5)=7t+12 | | 125oz=xcup | | (4x^3)+(33x^2)+(36x)=0 | | 2t-5=7t+12 | | 0-4=7(x-6) | | -4+(-y)=-2 | | logy=0.938 | | 2t-5=0 | | (4x^3)+(33x^2)+36x=0 | | 8x=5-3x | | h(x)=-.005x^2+25x |